Exploring diverse apple tree varieties in Kirov Region, Russia - Firsova Svetlana; Sofronov Alexandr; Rusinov Anatoly (BIO Web of Conferences)
The research was conducted in the experimental orchard of FARС North-East (Kirov) in the period from 2011 to 2022. The object of study - 11 varieties of apple trees. According to the winter hardiness, the variety Yunga was selected, which did not show any signs of frost during the period of study. In the group of varieties of summer ripening none of the examined samples did not surpass the control variety Grushovka Moskovskaya in productivity. In the group of varieties of fall maturity, the varieties Suvenir Altaya (55.77 kg/plant) and Novost Altaya (45.48 kg/plant) were identified by productivity, which significantly exceeded the control variety Borovinka (12.97 kg/plant). The maximum productivity of most fall varieties was observed in 2022, in the 16th year after planting. The variety Osennyaya radost’ with medium fruit size (111-150 g) was isolated during the study period. Most of the studied varieties are characterized by an attractive appearance. The varieties Osennyaya radost’, Novost Altaya (5 points), Severnaya zor’ka, Suvenir Altaya (4,5 points), Borovinka (4,3 points) deserve special attention. Selected variety Podarok sadovodam with dessert taste of fruits (5 points). Excellent taste of apples was noted in 3 other varieties: Osennyaya radost’ (4.8 points), Suvenir Altaya (4.7 points) and Krasnaya gorka (4.5 points).